Pengaruh Sosialisasi Terhadap Efektivitas Perilaku Wanita Pasangan Menikah Usia Dini dalam Penggunaan KB (Keluarga Berencana) di Wilayah Kerja Puskesmas Pakuan Baru - Sari, Deli Mala; Ningsih, Nisa Kartika; Lubis, Sunarti; Susanti, Desy (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The high number of child births and marriages in Indonesia today is a big problem and needs special attention in its handling to control the birth rate. One of the handling of high birth rates is the implementation of comprehensive development and family planning so that the behavior of using family planning becomes more effective. The effective use of family planning is influenced by several factors, including: knowledge, attitudes, number of children, income, husband's support, and support from health workers. The purpose of this study was to determine the factors that influence the behavior of early childhood couples in using family planning in the work area of the puskesmas Kotabaru.The research design is a quantitative study with a cross-sectional approach, which is carried out on a sample of 50 female couples of early age who were taken by purposive sampling. The chi-square analysis showed that there was a relationship between knowledge, income, husband's support, attitude, number of children , and support from health workers with the behavior of early married women in the use of family planning in the working area of Puskesmas Kotabaru.Through this research, the researchers suggested for the campaign to be more menggencarkan kb and improve the delivery of younger couples counseling to women in an effort to increase knowledge and disseminate, communication information and education (CIE) will benefit the use of contraception puskesmas Kotabaru.